The Pharmacological Mydriatic Pupil-to-Limbal Diameter Ratio as an Intuitive Predictor for the Risk of Intraoperative Floppy Iris Syndrome - Yurika Terauchi; Hiroshi Horiguchi; Takuya Shiba (Journal of Ophthalmology)
Purpose. To predict development of intraoperative floppy iris syndrome (IFIS) using the preoperative pharmacologically dilated pupil-to-limbal diameter (PL) ratio. Methods. The subjects were male patients treated by phacoemulsification who were or were not taking α1-adrenoceptor antagonists (ARAs). The PL ratio was calculated from the horizontal dilated pupil diameter and the horizontal corneal white-to-white distance measured by two observers in surgical videos. IFIS severity was graded using the criteria of Chang et al. We predicted the intuitive PL ratio to describe how precisely the experimenter can estimate the PL ratio without any tools. Results. There were 36 eyes in the α1-ARA group and 48 eyes in the control group. The pupil diameter and PL ratio were both significantly smaller in the α1-ARA group compared to the control group (p<0.001). All of pupil diameter, PL ratio, and intuitive PL ratio were negatively correlated with IFIS severity. The cutoff value for prediction of IFIS from the ROC curve was 7.20 mm for the pupil diameter, 58.7% for the PL ratio, and 62.5% for the intuitive PL ratio. The AUC for the ROC curve using the PL ratio (0.913) and intuitive PL ratio (0.892) did not perform substantially worse than that for the ROC curve based on the pupil diameter (0.875). Conclusions. The PL ratio is a simple and useful parameter for compensated prediction of IFIS development. Patients in whom this ratio is <60% are particularly likely to develop IFIS, and measures against onset of IFIS should be considered. This study is registered with UMIN000033012.